Innovative Assessment of Multiple Intelligences through Educational Games in Early Childhood Education - Jauharotur Rihlah; Afib Rulyansah; Andini Hardiningrum; Savira Zaniar (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This research aims to provide insights into how edugames can assess children’s cognitive abilities across various intelligence domains such as logical-mathematical, spatial, linguistic, interpersonal, and bodily-kinesthetic. Methodology: This study adopts a qualitative research design with a case study approach. Data were collected through semi-structured interviews with educators and edugame developers, classroom observations of students using the games, and document analysis. The study focused on a specific early childhood school institution where edugames were integrated into the curriculum. Thematic analysis was employed to identify key patterns and insights from the data. Main Findings: The findings reveal that edugames are effective in assessing a wide range of intelligences, engaging children in tasks that reflect different cognitive and social abilities. The games were particularly effective in evaluating logical-mathematical, spatial, linguistic, interpersonal, and bodily-kinesthetic intelligences. Educators reported that edugames allowed them to assess diverse abilities often overlooked by traditional assessment methods. However, challenges such as limited technological infrastructure and the need for adaptive features in games were identified. Novelty/Originality of this study: This research contributes to the emerging field of digital tools in early childhood education by presenting edugames as effective methods for assessing multiple intelligences. The implications for educational practice suggest that incorporating edugames into early childhood curricula can provide a more inclusive, dynamic, and accurate assessment of children's cognitive and social skills. Future research should focus on overcoming the identified challenges, such as the need for adaptive game features and better technological infrastructure.